EFFECTIVENESS OF COMPLEX DIAGNOSTIC METHODS FOR INFERTILITY OF INFLAMMATORY ORIGIN - Abdullayeva, L.M.; Abdiyeva, U.U. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Infertility of inflammatory origin is a pressing issue in modern reproductive medicine. According to global statistics, infertility affects approximately one in five couples, with inflammatory factors accounting for a significant proportion. This study aimed to assess the effectiveness of comprehensive modern diagnostic methods in detecting inflammation-related infertility. Materials and Methods: A total of 115 women were clinically evaluated and divided into three groups: Group I — primary infertility of inflammatory origin, Group II — secondary infertility, and Group III — clinically healthy women (control). Diagnostic tools included bacterioscopy, bacteriological culture, polymerase chain reaction (PCR), and functional methods such as ultrasonography and hysterosalpingography (HSG). Results: A history of inflammatory disease or sexually transmitted infections (STIs) was identified in 80% of women in the primary infertility group and 65% in the secondary infertility group. Bacterioscopy revealed inflammatory signs in 75% and 60% of cases, respectively. PCR and bacteriological analysis detected chlamydia, ureaplasma, and mycoplasma in 15–35% of Group I and 40–50% of Group II. HSG indicated tubal obstruction in 40% of Group I and 50% of Group II. Statistically significant differences were observed between clinical, laboratory, and instrumental parameters (p<0.05).